The Effect of Training and Work Motivation on Professionalism and Employee Performance at The Banjarmasin City Women's Empowerment and Child Protection Office - Ramadhan, Muhammad (LPPM Universitas Ekasakti, 2025)
This study aims to analyze the effect of training and work motivation on professionalism and employee performance at the Banjarmasin City Women’s Empowerment and Child Protection Office. The research employed a quantitative approach with a survey method. The population consisted of all employees in the office, and a saturated sampling technique was applied, resulting in 71 respondents. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares (PLS) (SmartPLS 3.2.0) to test both direct and indirect effects, with professionalism serving as a mediating variable. The findings reveal that training and work motivation have a positive and significant effect on both professionalism and employee performance. Professionalism also has a positive and significant impact on performance, mediating the relationship between training, work motivation, and performance, although the direct effects are more potent than the indirect effects. These results underscore the importance of enhancing training quality and effectively managing work motivation to promote professionalism and achieve optimal employee performance.